Directed C−H Halogenation Reactions Catalysed by PdII Supported on Polymers under Batch and Continuous Flow Conditions. Issue 59 (18th September 2019) - Majeed, Maitham H.; Shayesteh, Payam; Tunå, Per; Persson, Axel R.; Gritcenko, Roman; Wallenberg, L. Reine; Ye, Lei; Hulteberg, Christian; Schnadt, Joachim; Wendt, Ola F.
Abstract: A new generation of N ‐ heterocyclic carbene palladium(II) complexes containing vinyl groups in different positions in the backbone of the N ‐ heterocycle have been developed. The fully characterised monomers were copolymerised with divinylbenzene to fabricate robust polymer supported NHC‐Pd II complexes and these polymers were applied as heterogeneous catalysts in directed C−H halogenation of arenes with a pyridine‐type directing group. The catalysts demonstrated medium‐high catalytic activity with up to 90 % conversion and 100 % selectivity in chlorination. They are heterogeneous and recyclable (at least six times) with no significant leaching of palladium in batch mode catalysis. The best catalyst was also applied under continuous flow conditions where it disclosed an exceptional activity (90 % conversion) and 100 % selectivity for the mono‐halogenated product for at least six days, with no leaching of palladium, no loss of activity and an ability to maintain the original oxidation state of Pd II . Abstract : Supported NHC‐Pd II polymer catalyse C−H chlorination of arenes under batch and continuous flow conditions.